Pengaruh Discharge Planning Audiovisual Terhadap Tingkat Pengetahuan Dan Perilaku Self Care Management Pada Pasien Diabetes Mellitus Di Ruang Bedah RSI Darus Syifa’ Surabaya - Wijaya, Kartika Maharani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Diabetes mellitus is also called The Great Imitator because this disease can affect all organs of the body and cause various kinds of complications. At RSI Darus Syifa' Surabaya during January-October 2023 there were 452 diabetes mellitus patients undergoing inpatient treatment. The aim is to prove the effect of audiovisual discharge planning on the level of knowledge and self-care management behavior. This research uses a Quasy Experimental design with Pre-Post test Control Group Design. The population in this study were diabetes mellitus patients who were in the Surgical Room at RSI Darus Syifa' Surabaya. The samples were 33 for the control group and 33 for the treatment group. The sampling technique used purposive sampling, then the samples were divided into 2 groups, namely the intervention group (given audiovisual discharge planning) and the control group (given discharge planning according to the hospital). The independent variable in this study is audiovisual discharge planning. The dependent variable is the level of knowledge and self-care management behavior of diabetes mellitus. Data analysis used the Mann-Whitney U Test. Analysis of the Mann-Whitney U Test showed that the level of knowledge P value was 0.000 <0.05, meaning there was a difference between the intervention group and the control group. The self care management behavior variable obtained a level of knowledge P value of 0.001 < 0.05, meaning there was a difference between the intervention group and the control group. So that audiovisual discharge planning influences the level of knowledge and self-care management behavior in diabetes mellitus patients in the Surgical Room at RSI Darus Syifa' Surabaya.